Intention To Purchase Electronic Green Products Amongst Lecturers: An Empirical Evidence - Abdul Qader, Iman Khalid (2008)
The purpose of this study is to contribute to the body of knowledge in the area of green product purchase intention. Within the domain of Green marketing, where all activities are designed to generate and to facilitate any exchanges intended to satisfy human needs or wants, such that the satisfaction of these needs or wants occurs, with minimal detrimental impact on the natural environment.